2022
DOI: 10.1371/journal.pone.0265084
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the neuron to astrocyte ratio with cytostatics in hippocampal cell cultures from postnatal rats: A comparison of cytarabino furanoside (AraC) and 5-fluoro-2’-deoxyuridine (FUdR)

Abstract: Cell culture studies offer the unique possibility to investigate the influence of pharmacological treatments with quantified dosages applied for defined time durations on survival, morphological maturation, protein expression and function as well as the mutual interaction of various cell types. Cultures obtained from postnatal rat brain contain a substantial number of glial cells that further proliferate with time in culture leading to an overgrowth of neurons with glia, especially astrocytes and microglia. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Three to 4 h post-plating, culture medium was replaced with Neurobasal Plus basal medium supplemented with 2% B27 and 1% GlutaMAX. On day in vitro (DIV) 4, half of the conditioned medium was replaced by fresh Neurobasal Plus basal medium supplemented with 2% B27 and 1% GlutaMAX and 10 μM cytosine-arabinoside (AraC) at a final concentration of 5 μM AraC to inhibit glial proliferation ( Lesslich et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three to 4 h post-plating, culture medium was replaced with Neurobasal Plus basal medium supplemented with 2% B27 and 1% GlutaMAX. On day in vitro (DIV) 4, half of the conditioned medium was replaced by fresh Neurobasal Plus basal medium supplemented with 2% B27 and 1% GlutaMAX and 10 μM cytosine-arabinoside (AraC) at a final concentration of 5 μM AraC to inhibit glial proliferation ( Lesslich et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…We observed that at days in vitro 1 (DIV1), FABP7 positive glial cells are present in high numbers ( Figures 1A,B ) but are nearly absent by DIV7 ( Figures 1A,B ), consistent with our previous results ( Avraham et al, 2020 ). FDU treatment eliminates non-neuronal proliferating cells from the culture, without affecting neuronal properties and viability ( Lesslich et al, 2022 ). Consistently, we did not observe pycnotic nuclei in our FDU-treated cultures compared to no FDU.…”
Section: Resultsmentioning
confidence: 99%
“…On the subsequent in vitro day, the medium was further enhanced with 1 μm of cytarabino furanoside (AraC, C998100, TRC) for a duration of 24 h, to attenuate glial proliferation. Subsequently, medium was replenished with a fresh batch of coculture medium, with half-media changes implemented daily thereafter ( Goshi et al, 2020 ; Hasan & Berdichevsky, 2021 ; Lesslich et al, 2022 ). On the seventh day, the coculture medium was augmented with varied concentrations of N -acetyl-L-asparate (NAA; 1, 2.5, and 10 mM) or a vehicle control, and this was maintained for an additional 2 days.…”
Section: Methodsmentioning
confidence: 99%